Implicit expression refers to equation that are not strictly expressed in terms of y and x separately. In this case, the derivative of expression
<span>sqrt(xy)=x^2y+1 is
sqrt x * 0.5 y ^-0.5 dy + </span>sqrt y<span> * 0.5 x ^-0.5 dx= x^2 dy + 2xy dx
dy (x^2 - 0.5 (</span>x/y) ^0.5) = dx (2xy - 0.5 (y<span>/x)^0.5)
dy/dx = </span>(2xy - 0.5 (y/x)^0.5) / (x^2 - 0.5 (<span>x/y) ^0.5)</span>
Answer:
8 (7.94)
Step-by-step explanation:
You can think of it as a geometry problem.
What is formed here is a triangle, which sides ate: the line, the line's shadow, and the height from the ground to the kite (here I attach a drawing).
What you need to find is the height. We will call it H.
As the triangle formed is a right one, we can use Pitágoras' theorem. The height H squared plus the squared of the shadow is equal to the squared of the line (the hypotenuse). This is:
H^2 + 9^2 = 12^2
H^2 + 81= 144
H^2 = 63
Applying squared root in both sides
H = √63
H = 7,94
So, the height is approximately 8.
For this case we have that by definition, the standard form of the equation of the line is given by:

We have the following equation:

We manipulate the equation algebraically:

Finally, the equation is:

Answer:
